2020
DOI: 10.21203/rs.2.20730/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of 24 protocols for the production of platelet-rich fibrin

Abstract: Background The aim of this study was to evaluate 24 protocols for the production of platelet rich fibrin (PRF) produced via horizontal centrifugation to better understand cell separation following protocols at various times and speeds. Methods All protocols were compared utilizing a recent method to quantify cells in PRF in 1 mL sequential layers pipetted from the upper layer downwards until all 10 mL were harvested. In total, 960 complete blood counts (CBCs) were investigated. Both solid and liquid-based P… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Furthermore, it has been reported that different protocols and equipment may affect dramatically the biological signature and bone regeneration potential of platelet concentrates. 68,69 Such variability along with the high heterogeneity of clinical studies and the limitations of in vitro to in vivo extrapolations, warrants further well-designed pre-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been reported that different protocols and equipment may affect dramatically the biological signature and bone regeneration potential of platelet concentrates. 68,69 Such variability along with the high heterogeneity of clinical studies and the limitations of in vitro to in vivo extrapolations, warrants further well-designed pre-…”
Section: Discussionmentioning
confidence: 99%
“…Although L‐PRF have been extensively used in dentistry since first described by Choukroun and Dohan, 25 the exact biological mechanism of platelets derivates remains unclear in bone regeneration. Furthermore, it has been reported that different protocols and equipment may affect dramatically the biological signature and bone regeneration potential of platelet concentrates 68,69 . Such variability along with the high heterogeneity of clinical studies and the limitations of in vitro to in vivo extrapolations, warrants further well‐designed pre‐clinical and clinical investigations to further assess the biological effect of L‐PRF to promote bone regeneration and enhance the outcomes of implant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These subcategories represent the range of formulations produced by altering centrifugation protocols, with up to 24 protocols described in the literature for PRF alone. 46 The superfluous terminologies have been described as "disingenuous" by some experts who claim "PRP is PRP, whatever way you look at it." 47 There is concern in the scientific community that underlying commercial interests may lead to a cycle of reinventing the wheel.…”
Section: Discussionmentioning
confidence: 99%
“…Two from these did not report the centrifuge machine used (136,138). Two studies described two different protocols of centrifugation of solid/clot PRF in the high range using a fixed-angle centrifuge (132,133) or horizontal centrifugation (144). The protocol with the highest g-force was "1,000 g × 10 min'' (132).…”
Section: Protocols Of Centrifugation Reported With G-forcementioning
confidence: 99%
“…For example, based on the mathematical formulas stated in Table 9 (147), a slight increase in the r-max will significantly increase the g-force, ultimately affecting the final PRF generated in terms of cell content, size of clot, the distribution of the cells within the clot and indeed the entire morphology of the PRF clot. This was assessed by Miron et al who recently described that horizontal centrifugation yielded PRF with more accumulations of leukocytes and platelets in comparison to the PRF produced via the fixedangled technique (144).…”
Section: The Ar 2 T 3 Principles To Report the Centrifugation Of Platelet Concentratesmentioning
confidence: 99%